1990
DOI: 10.1212/wnl.40.10.1607
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of algorithms of testing for use in automated evaluation of sensation

Abstract: Estimates of vibratory detection threshold may be used to detect, characterize, and follow the course of sensory abnormality in neurologic disease. The approach is especially useful in epidemiologic and controlled clinical trials. We studied which algorithm of testing and finding threshold should be used in automatic systems by comparing among algorithms and stimulus conditions for the index finger of healthy subjects and for the great toe of patients with mild neuropathy. Appearance thresholds obtained by lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Since our study subjects were older than the pretest subjects, averaging the fourth and the fifth measurements was to guard against unstable measurements. Dyck et al [24] reported that appearance vibration thresholds obtained by linear ramps increasing at a rate less than 4.15 Ìm/s provided accurate and repeatable thresholds compared with those obtained by forcechoice testing. In this study, the increasing rates of our ramps were 0.83 Ìm/s for the validation and 1.66 Ìm/s for the normality study.…”
Section: Discussionmentioning
confidence: 99%
“…Since our study subjects were older than the pretest subjects, averaging the fourth and the fifth measurements was to guard against unstable measurements. Dyck et al [24] reported that appearance vibration thresholds obtained by linear ramps increasing at a rate less than 4.15 Ìm/s provided accurate and repeatable thresholds compared with those obtained by forcechoice testing. In this study, the increasing rates of our ramps were 0.83 Ìm/s for the validation and 1.66 Ìm/s for the normality study.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] This is due in part to a subject's reaction time. A subject needs to consciously perceive the stimulus, process the information, and generate an action to indicate a response.…”
mentioning
confidence: 99%
“…[23][24][25] VDT, CDT, and HP were assessed using the vibratory and thermal stimulators of a CASE IV™ system (WR Medical Electronics Co., Stillwater, MN), as previously described in detail. 20,[26][27][28] We did not assess warm perception thresholds in the study participants as our study protocol was already very extensive and time consuming and included evaluations beyond the scope of the current study. Moreover, warm perception thresholds assessed with the 4, 2, and 1 stepping algorithm and the CASE IV system showed a rather high intraindividual variability.…”
mentioning
confidence: 99%